The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/mds.26489
|View full text |Cite
|
Sign up to set email alerts
|

The Small GTPBinding Protein Rhes Influences Nigrostriatal‐Dependent Motor Behavior During Aging

Abstract: Our findings indicate a fine-tuning role of Rhes in regulating the number of TH-positive neurons of the substantia nigra and nigrostriatal-sensitive motor behavior during aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 23 publications
(49 reference statements)
3
22
0
Order By: Relevance
“…It was previously shown that lack of Rhes leads to a decrease of nigral TH-positive neurons accompanied by motor coordination deficits in male mice (Pinna et al, 2016 ). The present study provides insight into the factors contributing to neurodegeneration in Rhes KO mice by demonstrating that, besides the DAergic neurodegeneration, an increase in astrogliosis and microgliosis is present in these KO mice.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…It was previously shown that lack of Rhes leads to a decrease of nigral TH-positive neurons accompanied by motor coordination deficits in male mice (Pinna et al, 2016 ). The present study provides insight into the factors contributing to neurodegeneration in Rhes KO mice by demonstrating that, besides the DAergic neurodegeneration, an increase in astrogliosis and microgliosis is present in these KO mice.…”
Section: Discussionmentioning
confidence: 97%
“…Rhes mRNA is localized in striatal GABAergic medium-sized projection neurons of rodents and humans (Errico et al, 2008 ; Ghiglieri et al, 2015 ; Vitucci et al, 2015 ) and in large aspiny cholinergic interneurons (Sciamanna et al, 2015 ), where it modulates dopamine (DA)-dependent transmission. Recently, we have shown that Rhes mRNA is also expressed, although to a lesser extent, in tyrosine hydroxylase (TH)-positive neurons of the SNc and ventral tegmental area of the mouse midbrain (Pinna et al, 2016 ). Consistent with Rhes mRNA midbrain localization and its putative protective role in DAergic cell survival, male Rhes knockout (KO) mice have shown a reduction in TH-positive neurons in the SNc, associated with a progressive deficit in motor coordination and balance (Pinna et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A further support for a possible link between Rhes and Parkinson’s disease comes from recent findings indicating that this small GTPase is also expressed in a subset of tyrosine hydroxylase-positive neurons of the substantia nigra pars compacta, where its genetic ablation enhances vulnerability to age-dependent neuronal death in mutant mice [45]. Although the specific mechanism underpinning the relationship between Rhes and the survival of dopaminergic neurons is not clear, previous studies demonstrating its binding to beclin-1 [46] suggest a potential involvement of this G protein in cellular events implicated in neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%